From natural translation to translation competence: Pedagogical implications - Nakhli, Habiba (Arab Journal for Sciences and Research Publishing, 2023)
Translation is the first tool of communication between cultures and the means of knowledge transfer between different civilizations. It is recognized as a pillar of economic, scientific and social growth and its role in the prosperity of great nations throughout history is undeniable. At present time, with globalization and the technological progress that we know today, the need for competent translators, to ensure the quality and effectiveness of this communication, has become more evident. Because good performance depends on good quality of training, it is important to rethink the traditional methods that are used to teach translation and train translators. These methods tend to rely on memorization and intensive repetitive practice, rather than active learning through interaction, experimentation, and discovery. While such traditional methods reinforce the trainee translators’ linguistic abilities, they do not necessarily develop their ability to apply what they learn to new problems or real work situationsGiven the multifaceted task of translation, translation competence (TC) is conceived of as a multi-componential construct involving in addition to bilingual competence, a set of skills, attitudes and knowledge that allow the performance of a translation task effectively in a given context. Viewed this way, how can translation teachers/ trainers address and foster every aspect of TC?The present study investigates the development of the concept of TC and the implications it has for translator’s education.
Keywords: translation competence; native translator; translation competence acquisition; translation teaching